Positive Mechanisms of Enhancing Productivity of Education Quality - Abdullaeva Mukhayo Iskandarovna (Peerian Journals Publishing, 2023)
The article discusses the topics of creation of modern and proper system in nurture and education, importance of responsibility of parents and their collaboration with teachers, using foreign experience if tutoring, significance of national traditions and habits in nurturing.
Keywords: Innovation; development; education; nurture